Pathways from Physical Activity to Quality of Life in Older Women - McAuley, Edward (2008)
BACKGROUND: In spite of consistent evidence to suggest that being more physically active is associated with enhanced quality of life (QOL), there have been remarkably few attempts to determine the possible underlying mechanisms in this relationship. PURPOSE: To prospectively examine the roles played by self-efficacy and physical and mental health status in the physical activity and quality of life relationship in older women. METHOD: Older women (M age = 68.12 years) completed measures of physical activity, self-efficacy relative to balance, mental and physical health status, and global QOL at baseline (N = 249) and 24-month follow-up (N = 217). Demographics and general health information were assessed at baseline. A panel analysis within a covariance modeling framework was used to analyze the data. RESULTS: Analyses indicated that changes in physical activity over time were associated with residual changes in self-efficacy. Changes in self-efficacy were significantly associated with residual changes in physical and mental health status. Only changes in mental health status were significantly related to residual changes in global QOL. CONCLUSION: Results from this study support the role of self-efficacy in the relationship between physical activity and QOL. Future physical activity promotion programs should include strategies to enhance self-efficacy for physical activity to be most effective for this population.